Global Trends in Smart Healthcare and Smart Hospital Research: A Bibliometric and Systematic Literature Review Approach - Bahar Sangkur Gusasih; Faradilla Savitri Prasetyawati; Rafi Yasnova; Vip Paramarta; Farida Yuliaty (Advances in Human Resource Management Research, 2026)
Purpose: This study analyzes global research trends, intellectual structures, collaboration networks, technological themes, and future directions in smart healthcare and smart hospital research. Research Method: A bibliometric analysis combined with a Systematic Literature Review (SLR) based on the PRISMA protocol was employed. From 169 records identified in Scopus, ScienceDirect, Wiley Online Library, and Google Scholar, 26 international journal articles published between 2020 and 2025 met the inclusion criteria. VOSviewer was used to map keyword co-occurrence, thematic clusters, collaboration patterns, and temporal evolution of research. Results and Discussion: The findings indicate a substantial increase in smart healthcare publications, particularly during 2024–2025. Four dominant research clusters emerged: (1) artificial intelligence and healthcare analytics, (2) Internet of Medical Things (IoMT) and connected healthcare systems, (3) smart hospitals and healthcare information systems, and (4) digital twins, cybersecurity, sustainability, and healthcare governance. The results also reveal growing international and interdisciplinary collaboration among scholars in healthcare, engineering, computer science, and information systems. The overlay visualization shows a thematic shift from healthcare digitalization to intelligent healthcare ecosystems driven by AI, predictive analytics, digital twins, and sustainable innovations. Implications: This study provides a comprehensive overview of smart healthcare development and offers insights for policymakers, healthcare organizations, and technology developers in designing intelligent, secure, and sustainable healthcare systems. Originality: This study integrates bibliometric analysis and SLR to provide a holistic understanding of the evolution, intellectual structure, and future trajectory of smart healthcare and smart hospital research.